2014
DOI: 10.1371/journal.pone.0096809
|View full text |Cite
|
Sign up to set email alerts
|

Calponin-Like Chd64 Is Partly Disordered

Abstract: 20-hydroxyecdysone (20E) and juvenile hormone (JH) signaling pathways interact to regulate insect development. Recently, two proteins, a calponin-like Chd64 and immunophilin FKBP39 have been found to play a pivotal role in the cross-talk between 20E and JH, although the molecular basis of interaction remains unknown. The aim of this work was to identify the structural features that would provide understanding of the role of Chd64 in multiple and dynamic complex that cross-links the signaling pathways. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 58 publications
(111 reference statements)
0
18
0
Order By: Relevance
“…Chd64 is another protein previously known to bind to the JHRE and modulates the responses to JH exposure ( Li et al 2007 ). Although Chd64 possesses a clear calponin homology (CH) domain (pfam id: pfam00307), its relationship to the wider family of other CH-containing genes is largely uncataloged ( Kozłowska et al 2014 ). In our analysis, we have also identified putative Chd64 orthologs in the noninsect arthropods ( supplementary fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chd64 is another protein previously known to bind to the JHRE and modulates the responses to JH exposure ( Li et al 2007 ). Although Chd64 possesses a clear calponin homology (CH) domain (pfam id: pfam00307), its relationship to the wider family of other CH-containing genes is largely uncataloged ( Kozłowska et al 2014 ). In our analysis, we have also identified putative Chd64 orthologs in the noninsect arthropods ( supplementary fig.…”
Section: Resultsmentioning
confidence: 99%
“…The protein content and purity were evaluated after every stage of purification with SDS-PAGE57 and Coomassie Brilliant Blue R-250-stained gels58. The identification of the purified protein was performed by ESI-MS, as described previously4.…”
Section: Methodsmentioning
confidence: 99%
“…However, the molecular basis of the interactions between FKBP39, Chd64 and the other components of the multiprotein complex is not understood. Recently, Kozlowska et al 4. showed that the structure of Chd64 possesses a dual nature, consisting of a globular domain flanked by intrinsically disordered tails.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…melanogaster and T . castaneum are partly disordered; however, the extent and position of this disorder have not been defined [ 8 ]. Intrinsically disordered proteins (IDPs) and intrinsically disordered regions (IDRs) have been the focus of recent structure-function relationship studies [ 9 ].…”
Section: Introductionmentioning
confidence: 99%